An efficient Trojan delivery of tetrandrine by poly(N-vinylpyrrolidone)-block-poly(ε-caprolactone) (PVP-b-PCL) nanoparticles shows enhanced apoptotic induction of lung cancer cells and inhibition of its migration and invasion - Xu H (Dove Medical Press, 2013)
Huae Xu,1,2 Zhibo Hou,3 Hao Zhang,4 Hui Kong,2 Xiaolin Li,4 Hong Wang,2 Weiping Xie21Department of Pharmacy, 2Department of Respiratory Medicine, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 3First Department of Respiratory Medicine, Nanjing Chest Hospital, Nanjing, People's Republic of China; 4Department of Geriatric Gastroenterology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People's Republic of ChinaAbstract: Earlier studies have demonstrated the promising antitumor effect of tetrandrine (Tet) against a series of cancers. However, the poor solubility of Tet limits its application, while its hydrophobicity makes Tet a potential model drug for nanodelivery systems. We report on a simple way of preparing drug-loaded nanoparticles formed by amphiphilic poly(N-vinylpyrrolidone)-block-poly(ε-caprolactone) (PVP-b-PCL) copolymers with Tet as a model drug. The mean diameters of Tet-loaded PVP-b-PCL nanoparticles (Tet-NPs) were between 110 nm and 125 nm with a negative zeta potential slightly below 0 mV. Tet was incorporated into PVP-b-PCL nanoparticles with high loading efficiency. Different feeding ratios showed different influences on sizes, zeta potentials, and the drug loading efficiencies of Tet-NPs. An in vitro release study shows the sustained release pattern of Tet-NPs. It is shown that the uptake of Tet-NPs is mainly mediated by the endocytosis of nanoparticles, which is more efficient than the filtration of free Tet. Further experiments including fluorescence activated cell sorting and Western blotting indicated that this Trojan strategy of delivering Tet in PVP-b-PCL nanoparticles via endocytosis leads to enhanced induction of apoptosis in the non-small cell lung cancer cell A549 line; enhanced apoptosis is achieved by inhibiting the expression of anti-apoptotic Bcl-2 and Bcl-xL proteins. Moreover, Tet-NPs more efficiently inhibit the ability of cell migration and invasion than free Tet by down-regulating matrix metalloproteinases (MMP)-2 and MMP-9, as well as up-regulating tissue inhibitor of MMP-3 (TIMP-3). Therefore, data from this study not only confirms the potential of Tet in treating lung cancer but also offers an effective way of improving the anticancer efficiency of Tet by nanodrug delivery systems.Keywords: tetrandrine, poly(N-vinylpyrrolidone), lung cancer, nanoparticles